Polimorfisme Enzim Glucose-6-Phosphate Isomerase pada Tiga Populasi Tuna Sirip Kuning (Thunnus albacares) - Gusti Ngurah Permana; Jhon H. Hutapea; Sari Budi Moria; Haryanti Haryanti (Universitas Gadjah Mada, 2006)
Samples of yellowfin tuna (Thunnus albacares) were taken from three locations Bali, North Sulawesi and North Maluku. The glucose-6-phosphate isomerase (GPI) was analyzed from liver using allozyme electrophoresis method. Polymorphism of GPI enzyme was observed and four alleles (A, B ,C, D) were found in Bali population, three alleles (A,B,C) were found in North Maluku and North Sulawesi populations. Heterozygosity values, from Bali, North Maluku and North Sulawesi were 0.419; 0.417; 0.143 respectively. Genetic distance between North Sulawesi and North Maluku were 0.029, and with Bali population was 0.353. These results indicated that North Maluku and North Sulawesi population were not separate by geographic barrier, therefore genetic distance of both populations was closed. However, those populations were genetically separated to the Bali population might be due to major hydrological barrier.